Individual effect of shear rate and oxygen transfer on clavulanic acid production by Streptomyces clavuligerus - Ribeiro, Renata M. M. G. P.; Esperanca, Mateus N.; Sousa, Ana P. A. [UNESP]; Neto, Alvaro Baptista [UNESP]; Cerri, Marcel O. [UNESP] (Springer, 2021)
The production of biocompounds through the cultivation of filamentous microorganisms is mainly affected by Oxygen Transfer Rate (OTR) and shear rate ((gamma)overdot(av)) conditions. Despite efforts have been made to evaluate the effect of operating variables (impeller speed, N; and airflow rate, phi(air)) on clavulanic acid production, no analysis regarding the effect of OTR and (gamma)overdot(av) was made. Then, the aim of this study was to evaluate the dissociated effect of physical phenomena such as oxygen transfer and shear rate in the production of clavulanic acid from Streptomyces clavuligerus using a stirred tank bioreactor. Streptomyces clavuligerus cultivations were performed at five different OTR and (gamma)overdot(av) conditions by manipulating the operating conditions (N, phi(air), and gas inlet composition). Cultivations performed at equal impeller speed (600 rpm, similar (gamma)overdot(av)) using oxygen enrichment, showed that CA productivity (Prod(CA)) was positively affected by OTR increase. Subsequently, the different shear conditions (achieved by varying the impeller speed) lead to an increase in CA production levels. Despite both OTR and shear rate positively enhanced CA productivity, (gamma)overdot(av) exhibited the highest impact: an increase of 145% in OTRinitial enhanced the clavulanic acid productivity of about 29%, while an increment in the shear rate of 134% raised the Prod(CA) in 53%.
Keywords: Clavulanic acid; Shear rate; Oxygen transfer; Stirred tank bioreactor